Magnetic-pulse car body panels flattening. Theoretical aspects and practical results - Batygin, Yu.V.; Chaplygin, E.A.; Sabokar, O.S. (Електротехніка і електромеханіка, 2016)
The aim of the article is to provide theoretical and experimental studying of the «induction system with an attractive screen» practical effectiveness with the excited magnetic pulse attractive forces numerical estimation. Originality. For the first time, the theoretical analysis of the electrodynamics process for the «inductor system with attractive screen» at the low frequent assumption were conducted. Methodology of the analysis applied is based on the classic electrodynamics circuits theory. All of the resulted carried out, were obtained as the Maxwell’s differential equation solutions and its behavior was analyzed analytically. Results. The electrodynamics process was analyzed and the principle efficiency of the «induction system with an attractive screen» as an effective tool for magnetic pulse forming of the thin sheet metals was substantiated. The axis distributions of the attractive forces based on the relations been obtained were illuminated graphically. The results of experimental testing of the system in the engineering operation of the external non-contact dents removing on the car body panels samples were presented. Practical value. According to the results of the calculation analyses the fundamental workability of the «inductor system with attractive shield» as an effective magnetic pulse sheet metal part attraction tool was proved. It was shown that the not deep metal surface damages could be worked up by magnetic pulses technologies with a high performance in a short time.